Transformasi Budaya Dalam Al-Qur’an - Hakim, Nurul (Dialogia: Jurnal Studi Islam dan Sosial, 2016)
Abstract: Everyone wants to have prosperity in their life. But in the point of fact, not all people are able to fulfill their fancy. As the result, such question rises "Why do all fancies have not been fulfilled?" To overcome that problem, Al-Qur’an offers a solution that discusses about concept of fulfillment. This concept draws the movement of human mindset and it called as Cultural transformation. Moreover, mindset is the basic fundamental and its fundamental affects other aspects of human life. Furthermore, they are four terms of culture such cultural values, cultural systems, social system, physical culture (elements of physical cultures).  While cultural values are defined as vantage of life, priority, time allotment, human point of views, and natural views.